Fibrinolytic activation markers predict myocardial infarction in the elderly. The Cardiovascular Health Study. - Cushman, M; Lemaitre, R N; Kuller, L H; Psaty, B M; Macy, E M; Sharrett, A R; Tracy, R P (Arterioscler Thromb Vasc Biol, 1999)
Coagulation factor levels predict arterial thrombosis in epidemiological studies, but studies of older persons are needed. We studied 3 plasma antigenic markers of fibrinolysis, viz, plasminogen activator inhibitor-1 (PAI-1), fibrin fragment D-dimer, and plasmin-antiplasmin complex (PAP) for the prediction of arterial thrombosis in healthy elderly persons over age 65. The study was a nested case-control study in the Cardiovascular Health Study cohort of 5201 men and women >/=65 years of age who were enrolled from 1989 to 1990. Cases were 146 participants without baseline clinical vascular disease who developed myocardial infarction, angina, or coronary death during a follow-up of 2.4 years. Controls remained free of cardiovascular events and were matched 1:1 to cases with respect to sex, duration of follow-up, and baseline subclinical vascular disease status. With increasing quartile of D-dimer and PAP levels but not of PAI-1, there was an independent increased risk of myocardial infarction or coronary death, but not of angina. The relative risk for D-dimer above versus below the median value (>/=120 microg/L) was 2.5 (95% confidence interval, 1.1 to 5.9) and for PAP above the median (>/=5.25 nmol/L), 3.1 (1.3 to 7.7). Risks were independent of C-reactive protein and fibrinogen concentrations. There were no differences in risk by sex or presence of baseline subclinical disease. D-dimer and PAP, but not PAI-1, predicted future myocardial infarction in men and women over age 65. Relationships were independent of other risk factors, including inflammation markers. Results indicate a major role for these markers in identifying a high risk of arterial disease in this age group.
Keywords: Age Factors; Aged; Angina Pectoris; Biomarkers; Female; Fibrin Fibrinogen Degradation Products; Fibrinolysin; Fibrinolysis; Follow-Up Studies; Heart Arrest; Humans; Male; Myocardial Infarction; Plasminogen Activator Inhibitor 1; Risk Factors